Vitamin D - is there a correlation between vitamin D level in serum and caries? - review of the literature with analysis of survey among Polish adults about supplementation of vitamin D - Patrycja Łanowy; Katarzyna Mocny-Pachońska; Agata Trzciona; Marta Tanasiewicz (Kazimierz Wielki University, 2019)
Introduction: Caries is a common disease with a complex etiology, classified as a civilization disease. In Poland, it affects up to 90% of children. According to research, 99.9% of Poles between 34 and 44 years old have or have been suffering from caries - moreover, only 5.4% of those in the group have full dentition. An important role in the resistance to caries is adequate mineralization of hard tissues. The relationship between the level of vitamin D, which participates in proper bone mineralization and the presence of caries in the oral cavity, has been studied for years. In Poland, it is recommended to supplement vitamin D in children and adults from September to May and the whole year if skin production is insufficient. Material and methods: The analysis of the correlation between the occurrence of caries and the level of vitamin D in the blood serum was made on the basis of articles published in the last 7 years, available in the database PubMed. Results: Available researches from last seven years suggest strong correlation between level of vitamin D in serum and occupancy of caries among children.